Characteristics of Shigatoxin-Producing Escherichia coli Strains Isolated during 2010–2014 from Human Infections in Switzerland - Fierz, Lisa; Cernela, Nicole; Hauser, Elisabeth; Nüesch-Inderbinen, Magdalena; Stephan, Roger (Frontiers in Microbiology, 2017)
Objectives: The aim of this study was to characterize a collection of 95 Shigatoxin-producing E. coli (STEC) isolated from human patients in Switzerland during 2010–2014. Methods: We performed O and H serotyping and molecular subtyping. Results: The five most common serogroups were O157, O145, O26, O103, and O146. Of the 95 strains, 35 (36.8%) carried stx1 genes only, 43 strains (45.2%) carried stx2 and 17 (17.9%) harbored combinations of stx1 and stx2 genes. Stx1a (42 strains) and stx2a (32 strains) were the most frequently detected stx subtypes. Genes for intimin (eae), hemolysin (hly), iron-regulated adhesion (iha) and the subtilase cytotoxin subtypes subAB1, subAB2-1, subAB2-2 or subAB2-3 were detected in 70.5%, 83.2%, 74.7% and 20% of the strains, respectively. Multilocus sequence typing assigned the majority (58.9%) of the isolates to five different clonal complexes (CC), 11, 32, 29, 20, and 165, respectively. CC11 included all O157:[H7] and O55:[H7] isolates. CC32 comprised O145:[H28] isolates, and O145:[H25] belonged to sequence type (ST) 342. CC29 contained isolates of the O26:[H11], O111:[H8] and O118:[Hnt] serogroups, and CC20 encompassed isolates of O51:H49/[Hnt] and O103:[H2]. CC165 included isolates typed O80:[H2]-ST301, all harboring stx2d, eae-xi, hly, and 66.7% additionally harboring iha. All O80:[H2]-ST301 strains harbored at least 7 genes carried by pS88, a plasmid associated with extraintestinal virulence. Compared to data from Switzerland from the years 2000–2009, an increase of the proportion of non-O157 STEC infections was observed as well as an increase of infections due to STEC O146. By contrast, the prevalence of the highly virulent German clone STEC O26:[H11]-ST29 decreased from 11.3% during 2000-2009 to 1.1% for the time span 2010-2014. The detection of O80:[H2]-ST301 harboring stx2d, eae-xi, hly, iha, and pS88 related genes suggests an ongoing emergence in Switzerland of an unusual, highly pathogenic STEC serotype. Conclusions: Serotyping and molecular subtyping of clinical STEC demonstrate that although STEC O157 predominates among STEC isolated from diseased humans, non-O157 STEC infections are increasing in Switzerland, including those due to STEC O146:[H2/H21/H28]-ST442/ST738 harboring subAB variants, and the recently emerged STEC O80:[H2]-ST301 harboring eae-xi and pS88 associated extraintestinal pathogenic virulence genes.